Green Concrete: Ferrock Applicability and Cost- Benefit Effective Analysis - Hadi, Arzu M.; Hasan, Kamalaldin F.; Ahmed, Inas M.; Meteab, Maha A.; Hasan, Qais F. (Bumi Publikasi Nusantara, 2023)
This research aims to assess the viability and suitability of Ferrock as an alternative to concrete for constructing foundations. The study evaluates the performance of Ferrock in foundation applications, compares its costs with traditional concrete, and examines the benefits of using Ferrock for foundations. To achieve these objectives, the utilization of Staad Pro and Foundation software is done to analyze the performance of Ferrock foundations. A cost-benefit analysis, considering factors like material costs, construction techniques, and maintenance requirements to determine the economic feasibility of Ferrock as a substitute for concrete and the potential to reduce carbon emissions, and promote environmentally friendly construction practices is also done. The research findings indicate that Ferrock exhibits promising performance characteristics for building foundations. It demonstrates comparable strength to traditional concrete while offering potential environmental benefits. Although implementing Ferrock may require an initial investment, the long-term advantages of reduced maintenance costs and improved sustainability contribute to its overall value proposition.